Effect of temperature perturbation on hydrogen bonding in aqueous solutions of different urea concentrations1. Issue 73 (9th August 2015) - Mafy, Noushaba Nusrat; Afrin, Tanjina; Rahman, M. Muhibur; Mollah, M. Yousuf A.; Susan, Md. Abu Bin Hasan
<x xml:space="preserve">Abstract</x> Water structure modifications with urea and temperature have been studied in aqueous solution by analyzing changes in hydrogen bonding and the extent of aggregation.